Dextral Strike‐Slip and Normal Faulting During Middle Miocene Back‐Arc Extension and Westward Anatolia Extrusion in Central Greece. Issue 6 (25th May 2021) - Faucher, Agathe; Gueydan, Frédéric; Jolivet, Marc; Alsaif, Manar; Célérier, Bernard
Abstract: The present‐day Aegean tectonic configuration is marked by the interplay between Hellenic slab rollback and Anatolian extrusion, explaining the formation of extensional basins and dextral strike‐slip faults. We aim to constrain middle Miocene activity of dextral strike‐slip and normal faults in Central Greece with structural analysis and low‐temperature data. We show that onshore middle Miocene basins are controlled by both NW‐striking normal faults and NE‐striking dextral strike‐slip faults. E‐striking normal faults developed during the Plio‐Quaternary inside pre‐existing NW‐striking fault zones. Stress tensor calculations show that in the middle Miocene, NW‐striking normal faults and NE‐striking dextral faults are compatible, confirming their coeval activity. In contrast, the Plio‐Quaternary stress tensor suggests an almost N‐S radial extension, which is not compatible with NE‐striking dextral faults in Central Greece. Apatite fission‐track data additionally constrain middle Miocene local cooling near NW‐striking normal faults. They also support a difference in the amount of exhumation between Central Greece and the Cyclades, likely accommodated by the Pelagonian dextral strike‐slip fault. We propose that in the middle Miocene, the co‐existence of dextral strike‐slip and normal faults is associated with an almost N‐S extension related to trench retreat and an E‐W compression related to westward extrusion of Anatolia. The progressive trench curvature during rollback implies block rotation, accommodated by the Pelagonian fault, and subsequent normal fault and extensional stress rotation. During the Plio‐Quaternary, a change in extensional direction from NE‐SW to N‐S implies the formation of E‐striking normal faults inside NW‐striking fault zones, defining oblique rift systems. Key Points: Central Greece middle Miocene basins are controlled by the coeval activity of NE‐striking dextral strike‐slip and NW‐striking normal faults The middle Miocene Pelagonian dextral strike‐slip fault accommodated the differential extension rate between the Cyclades and Central Greece Plio‐Quaternary deformation is controlled by E‐striking normal faults and NW‐striking fault zones, forming oblique rifts (Evvia, Corinth)